Adolescent leadership self-efficacy and future orientation correlates: contingencies of race and parental educational attainment - Mingola, Nicole, author; MacPhee, David, advisor; Walker, Aimee, committee member; Peila-Shuster, Jackie, committee member (Colorado State University. Libraries, 2022)
Using a Positive Youth Development (PYD) framework to guide this research, it is critical that adolescents develop skills for attaining leadership self-efficacy and a positive future orientation. Historically, adolescents marginalized by race or socioeconomic status may not be presented with the same developmental opportunities as their counterparts. The purpose of this research is to examine the relationship between adolescent leadership self-efficacy and future orientation while identifying contingencies by race and/or parental educational attainment. The sample of predominantly Black, Indigenous and people of color (BIPOC) adolescents was obtained from a secondary dataset from a family leadership program. Results highlight a strong positive relationship between leadership self-efficacy and future orientation among adolescents contemporaneously and over time. Moderation by parental educational attainment, but not by race, was supported. Strengths, limitations, and future directions are discussed.